Neuroendocrine Tumor, Well Differentiated, of the Breast: A Relatively High-Grade Case in the Histological Subtype - Shogo Tajima; Hajime Horiuchi (Case Reports in Pathology)
Primary neuroendocrine carcinoma of the breast is a rare entity, comprising <1% of breast carcinomas. Described here is the case of a 78-year-old woman who developed an invasive tumor in the left breast measuring 2.0 cm x 1.5 cm x 1.2 cm. The tumor was composed of only endocrine elements in the invasive part. It infiltrated in a nested fashion with no tubular formation. Intraductal components were present both inside and outside of the invasive portion. Almost all carcinoma cells consisting of invasive and intraductal parts were positive for synaptophysin and neuron-specific enolase. According to the World Health Organization classification 2012, this tumor was subclassified as neuroendocrine tumor, well-differentiated. Among the subgroup, this tumor was relatively high-grade because it was grade 3 tumor with a few mitotic figures. Vascular and lymphatic permeation and lymph node metastases were noted. In the lymph nodes, the morphology of the tumor was similar to the primary site. No distant metastasis and no relapse was seen for one year after surgery. The prognosis of neuroendocrine carcinomas is thought to be worse than invasive mammary carcinomas, not otherwise specified. Therefore, immunohistochemistry for neuroendocrine markers is important in the routine practice to prevent overlooking neuroendocrine carcinomas.